Analisis Perbandingan Tingkat Kesehatan Perbankan Di Bursa Efek Indonesia Menggunakan Metode Rbbr (Risk Bassed Bank Rating) - Claudia, Cindy; Susanti, Nawal Ika (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The health of the bank is a reflection of the condition and performance of a bank. Referring to Bank Indonesia Regulation No. 13/PBI/2011 there are four components to know the condition of the bank's health level, namely Risk Profile, Good Corporate Governance, Earning, and Capital. The focus of research in writing this thesis is how the analysis of the comparative health levels of Islamic Banks and Conventional Banks in the first quarter of 2019- second quarter 2020 on the Indonesia Stock Exchange uses the RBBR method. The focus of research in writing this thesis is how the analysis of the comparative health levels of Islamic Banks and Conventional Banks in the first quarter of 2019- second quarter 2020 on the Indonesia Stock Exchange uses the RBBR method. The research object consists of 6 banks going public on the Indonesia Stock Exchange, namely BTPS, BRIS, PNBS, BCA, BRI, BNI with quantitative approach methods that are descriptive of analysis. The data used is secondary data. Factors tested in the study were NPF/NPL, FR/LDR, ROA, ROE, BOPO, CAR, and GCG. The hypothesis test used is the Mann Whitney U Test with a significant level of 5%. Descriptive statistical test results on NPF/NPL, FDR/LDR, ROA, ROE, BOPO factors show that Conventional Banks are healthier compared to Islamic Banks. GCG shows that Islamic Banks and Conventional Banks alike have the same title of SEHAT, and car shows that Islamic banks are healthier compared to conventional banks. The results of the hypothesis test using the Mann Whitney U Test showed that there was no significant comparison in the ratio of NPF/NPL, FDR/LDR, ROA, CAR GCG Islamic Bank and Conventional Bank, on ROE and BOPO showing that there was a significant comparison between Islamic Bank and Conventional Bank.